1996
DOI: 10.1111/j.1600-0668.1996.t01-1-00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion of Automotive Alternative Fuel Vapors within a Residence and Its Attached Garage

Abstract: A study was undertaken to investigate the use of mass balance modeling techniques to predict air pollution concentrations in residential settings where the source is evaporative emissions of alternative fuels emitted in the attached garage. Field study measurements of the spatial and temporal distribution of evaporative emissions in an attached garage were used to conduct this investigation. In this field study, known quantities of methanol were allowed to evaporate in the garage. Methanol concentrations were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…A number of studies have reported vehicles parked in attached garages as an important source of toxic organic compounds inside residences (Hawthorne et al 1986; Thomas et al 1993;Lansari et al 1996;Tsai and Weisel 2000;Mann et al 2001;Graham et al 2004;Dodson et al 2008). In addition to vehicles, people often store gasoline, yard, and garden supplies in garages, which can also be a source of volatile organic compounds (VOC, Batterman et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies have reported vehicles parked in attached garages as an important source of toxic organic compounds inside residences (Hawthorne et al 1986; Thomas et al 1993;Lansari et al 1996;Tsai and Weisel 2000;Mann et al 2001;Graham et al 2004;Dodson et al 2008). In addition to vehicles, people often store gasoline, yard, and garden supplies in garages, which can also be a source of volatile organic compounds (VOC, Batterman et al 2006).…”
Section: Introductionmentioning
confidence: 97%
“…CONTAM provides dynamic simulations of inter-zonal airflow, ventilation rates, and concentrations of gaseous and aerosol pollutants. The performance of the model has been evaluated extensively (Lansari et al, 1996;Emmerich and Nabinger, 2000;Emmerich et al, 2003;Howard-Reed et al, 2004. Of particular relevance to our application, Emmerich et al (2003) and Emmerich and Nabinger, (2000) found that modeled average fine particle levels were within 30% of the measured values during a study of air cleaner performance in a single-zone test home.…”
Section: Indoor Air Quality Simulationmentioning
confidence: 99%
“…CO emissions in the context of accidental deaths or suicide attempts 1,2 and fuel vapors evaporating from vehicles [3][4][5] were the topics of studies reported at the time. These studies reported on a limited number of measurements, usually a single vehicle in a single garage; tracer studies using sulfur hexafluoride (SF 6 ); or modeling estimates based on assumed conditions of emission rate and house volume.…”
Section: Introductionmentioning
confidence: 99%